Hepatitis B virus quasispecies evolution after liver transplantation in patients under long‐term lamivudine prophylaxis with or without hepatitis B immune globulin. Issue 2 (April 2015) - Buti, M.; Tabernero, D.; Mas, A.; Homs, M.; Prieto, M.; Rodríguez‐Frías, F.; Casafont, F.; Casillas, R.; González, A.; Miras, M.; Herrero, J.I.; Castells, L.; et al.
Abstract: Aims: To investigate an optimal long‐term prophylactic strategy for prevention of hepatitis B virus (HBV) recurrence after liver transplantation, we conducted a randomized study of 29 transplant recipients receiving a short course of hepatitis B immune globulin (HBIg) + lamivudine (LAM), followed by randomization to long‐term prophylaxis with LAM with or without HBIg. Methods: The efficacy and safety, and impact on survival and HBV recurrence of these 2 prophylactic regimens were compared over a mean period of 10 years. In patients with viral recurrence, the HBV quasispecies in the surface/polymerase region were studied by ultra‐deep pyrosequencing (UDPS). Results: The 10‐year survival rate was 76% and was not affected by the type of prophylaxis. Four patients had hepatitis B surface antigen (HBsAg) recurrence within the first 48 months after orthotopic liver transplantation (OLT). HBsAg‐positive and ‐negative patients showed similar mean survival times, with no differences between the 2 regimens. Low HBV DNA levels were transiently detected in 32% of HBsAg‐negative patients. UDPS showed major changes after OLT in the HBV quasispecies of patients with viral recurrence, which may be explained by a "bottleneck" effect of OLT together with prophylactic therapy. Conclusion: Long‐term survival after OLT in end‐stage chronic hepatitis B patients was good with both prophylactic strategies. However, low, transient HBV DNA levels were detected even in the absence of HBsAg, showing the importance of continuing HBV prophylaxis.